Assessment of the ergogenic effect of caffeine supplementation on mood, anticipation timing, and muscular strength in older adults. Issue 3 (29th August 2013) - Tallis, Jason; Duncan, Michael J.; Wright, Sheila Leddington; Eyre, Emma L. J.; Bryant, Elizabeth; Langdon, Dominic; James, Rob. S.
Abstract The effect of caffeine to promote improvements in mood, cognition, and exercise performance has been well established in young and athletic adults. However, little is known about whether such nutritional ergogenic aids are effective in enhancing psychological well‐being, physiological or cognitive performance in older adults. This study assesses the ergogenic effect of caffeine on mood, perceptual‐motor coupling, and muscular strength in an older human population. Following a familiarization session, 12 apparently healthy volunteers (nine females and three males; 69 ± 6 years) completed two laboratory visits. "Pre ingestion" trials of mood state Brunel Mood State Inventory (BRUMS) and coincidence anticipation performance (Bassin anticipation timer) at slow (3 mph) and fast (8 mph) stimulus speeds were completed on both visits. Using a randomized, double‐blind, cross‐over design, participants consumed either caffeine (3 mg/kg body mass) or a placebo. Sixty minutes postingestion participants repeated the trials before completing a set of 10 consecutive repetitions of maximal knee extension using isokinetic dynamometry. Rating of perceived exertion (RPE) was assessed following the fifth and final repetition. Caffeine ingestion significantly improved mood state scores for vigor by 17% (P = 0.009) and reduced absolute error by 35% (P = 0.045) during coincidence anticipation assessment at 8 mph compared to placebo. There were no other significant effects. Caffeine ingestion failed to augment maximal voluntary contraction of the knee extensors and RPE did not prove to be significantly different to from placebo (P > 0.33 in each case). Acute caffeine ingestion may not be an effective ergogenic aid for improving muscular strength in older adults but could possibly be used as a nutrition supplement for enhancing mood and improving cognitive performance in daily living tasks where interceptive timing skills are required.